2010
DOI: 10.1002/jcp.22024
|View full text |Cite
|
Sign up to set email alerts
|

NF‐κB activation stimulates osteogenic differentiation of mesenchymal stem cells derived from human adipose tissue by increasing TAZ expression

Abstract: Tumor necrosis factor-alpha (TNF-alpha) is a skeletal catabolic agent that stimulates osteoclastogenesis and inhibits osteoblast function. Although TNF-alpha inhibits the mineralization of osteoblasts, the effect of TNF-alpha on mesenchymal stem cells (MSC) is not clear. In this study, we determined the effect of TNF-alpha on osteogenic differentiation of stromal cells derived from human adipose tissue (hADSC) and the role of NF-kappaB activation on TNF-alpha activity. TNF-alpha treatment dose-dependently incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
148
2
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 172 publications
(163 citation statements)
references
References 48 publications
8
148
2
2
Order By: Relevance
“…31 On the contrary, Cho et al demonstrated that NF-kB activated by TNF-a promoted osteogenesis through upregulation of a transcriptional coactivator with PDZ-binding motif (TAZ) in adipose-derived MSCs. 33 In our experimental model, we confirmed that the genes involved in osteogenic regulation were suppressed by NF-kB decoy ODN (Supplementary Fig. S2).…”
Section: Figsupporting
confidence: 72%
See 1 more Smart Citation
“…31 On the contrary, Cho et al demonstrated that NF-kB activated by TNF-a promoted osteogenesis through upregulation of a transcriptional coactivator with PDZ-binding motif (TAZ) in adipose-derived MSCs. 33 In our experimental model, we confirmed that the genes involved in osteogenic regulation were suppressed by NF-kB decoy ODN (Supplementary Fig. S2).…”
Section: Figsupporting
confidence: 72%
“…30 Previous reports suggested that TNF-a enhances osteoclastogenesis and inhibits osteogenesis at an early stage of inflammation, but induces osteogenesis at the later tissue repair stages of inflammation. 30 The role of NF-kB in osteogenesis in previous reports [31][32][33][34][35] and our current findings may be due to different time points of evaluation, different proinflammatory stimuli, and the specific osteogenic markers tested.…”
Section: Figmentioning
confidence: 66%
“…ASC can be osteogenic differentiated by chemical stimulation using media supplements and growth factors to induce lineage specification, such as 1, 25-dihydroxyvitamin D3 (VD3), dexamethasone, β-glycerolphosphate and ascorbic acid (3, 63, 94). Besides, additional growth factors and components including BMP-2, growth and differentiation factor-5, retinoic acid, and tumor necrosis factor-α among others have also been researched as osteogenic stimulators (31,(95)(96)(97). However, the differentiation procedure has the shortcomings of requiring additional culture time and steps including the use of large amounts of costly growth factors and some supplements which could be cytotoxic to cells, before implantation to achieve therapeutic efficacy.…”
Section: Osteogenesis Of Ascs Via Stimulationmentioning
confidence: 99%
“…[60][61][62][63] MicroRNAs regulate proliferation and differentiation of MSC; 64 miR-125b, miR-146a and miR-196a affect osteogenic differentiation and cell proliferation. [65][66][67] Adipogenic differentiation is stimulated by miR-143 68 and miR-204 69 whereas miR-21 and miR-27 have been shown to down-regulate adipogenesis by directly targeting the adipogenic transcription factor PPARG. 70,71 Recently, Bork and co-workers 72 have for the first time identified miR-369-5p and miR-371 as two additional adipogenic regulators.…”
Section: Mirnas In the Hematopoietic Stem Cell Nichementioning
confidence: 99%